Palladium Complexes Bearing Mesoionic Carbene Ligands: Applications in α‐Arylation, α‐Methylation and Suzuki–Miyaura Coupling Reactions. Issue 1 (7th December 2015) - Maity, Ramananda; Verma, Amit; van der Meer, Margarethe; Hohloch, Stephan; Sarkar, Biprajit
Abstract: Complexes of mesoionic carbene (MIC) ligands are gaining immense popularity in organometallic chemistry and homogeneous catalysis. We present here a series of palladium(II) complexes that are comprised of MIC donor ligands, and we demonstrate their applications in α‐arylation, α‐methylation, and Suzuki–Miyaura coupling reactions. All the complexes have been structurally characterized by X‐ray crystallographic analysis. These palladium(II) complexes are potent precatalysts and they deliver good to excellent yields for both α‐arylation and Suzuki–Miyaura coupling reactions. A palladium(II) complex bearing two MIC units in a trans fashion is used for chemoselective Suzuki–Miyaura coupling reaction. This complex delivers lower yields in α‐arylation reactions compared with PEPPSI‐type complexes, however, it gives an α‐methylated product when the reaction is conducted in N, N ‐dimethylformamide. Mercury poisoning experiments suggest that the Suzuki–Miyaura coupling reaction likely proceeds via Pd nanoparticles. However, the α‐arylation reaction proceeds homogeneously, as shown by the negative mercury poison test. The present results thus open up new avenues for MIC ligands in catalytic α‐arylation and α‐methylation reactions. Abstract : A series of palladium(II) complexes comprised of mesoionic carbene donor ligands is presented along with their applications in α‐arylation, α‐methylation, and Suzuki–Miyaura coupling reactions.